Effect of Bath Temperature on Optical and Morphology Properties of CdS Thin Films Grown by Chemical Bath Deposition. (March 2017) - Rondiya, Sachin; Rokade, Avinash; Gabhale, Bharat; Pandharkar, Subhash; Chaudhari, Madhavi; Date, Abhijit; Chaudhary, Minakshi; Pathan, Habib; Jadkar, Sandesh
Abstract: Synthesis of CdS thin films were carried out onto glass substrates by chemical bath deposition (CBD) method using CdCl2 asCd 2+ and thiourea as S 2- ion source with ammonia as a complexing agent. Influence of bath temperature on structural, morphology and optical properties has been systematically and carefully investigated. XRD analysis revealed that the synthesizedCdS films are nanocrystalline having hexagonal structure with (002) preferential orientation. Estimated crystallite size was foundin the range 16-32 nm. The UV-Visible spectroscopy analysis showed that the films have high transmission (> 70%) in visibleand NIR region of solar spectrum. Optical band gap was found > 2.3 eV over the entire range of bath temperature studied. TheRaman spectra for the CdS films deposited at various bath temperatures shows a continuous shift of 1 LO phonon peak towardshigher frequency which suggest the improvement of structural order with increase in bath temperature. The increase in theintensity ratio, 2LO/1LO with bath temperature indicates enhancement of crystallinity of CdS films with increase in bathtemperature. The SEM analysis showed that CdS films deposited at various bath temperatures are smooth, homogeneous, andnearly uniform with randomly oriented spherical nanocrystallites.